Fruit Volatile Profiles of Two Citrus Hybrids Are Dramatically Different from Those of Their Parents - Rambla, Jose L.; González-Mas, María C.; Pons, Clara; Bernet, Guillermo P.; Asins, María J.; Granell, Antonio (2017)
Volatile compounds released from the fruit of two hybrid Citrus genotypes (FxCh90 and FxCh77) were compared to those from their parental varieties, Fortune mandarin and Chandler pummelo. A series of 113 compounds were identified, including 31 esters, 23 aldehydes, 20 alcohols, 17 monoterpenoids, and other compounds. The differences in the volatile profile among these four genotypes were essentially quantitative. The most striking result was that the volatile profile of the hybrids was not intermediate between their parents and completely differed from that of Chandler, but came closer to Fortune. This was because 56 of the 113 volatile compounds in the hybrids showed significantly higher or lower levels than in any of the parents. Such transgressive behavior in these hybrids was not observed for other fruit quality traits, such as acidity or soluble solid content. The combination of volatile profiling and chemometrics can be used to select new Citrus genotypes with a distinct volatile profile.